rTMS Reduces Psychopathological Burden and Cocaine Consumption in Treatment-Seeking Subjects With Cocaine Use Disorder: An Open Label, Feasibility Study - Pettorruso, Mauro; Martinotti, Giovanni; Santacroce, Rita; Montemitro, Chiara; Fanella, Fabrizio; di Giannantonio, Massimo; , the rTMS stimulation group; De Risio, Luisa; Petrucci, Ilaria; Tourjansky, Gaia; Capicotto, Patrizia; Neri, Francesca; et al. (Frontiers in Psychiatry, 2019)
Introduction: Cocaine use disorder (CUD) currently represents a notable public health concern, linked with significant disability, high chances of chronicity, and lack of effective pharmacological or psychological treatments. Repetitive transcranial magnetic stimulation (rTMS) is supposed to be a potential therapeutic option for addictive disorders. Aim of this study was to evaluate the feasibility of rTMS on (1) cocaine craving and consumption and (2) other comorbid psychiatric symptoms. Methods: Twenty treatment seeking CUD subjects underwent 2 weeks of intensive rTMS treatment (15Hz; 5 days per week, twice a day for a total of 20 stimulation sessions) of the left dorsolateral prefrontal cortex, followed by 2 weeks of maintenance treatment (15Hz, 1 day per week, twice a day). Sixteen patients completed the study. Patients were evaluated at baseline (T0), after 2 weeks of treatment (T1), and at the end of the study (T2; 4 weeks), with the following scales: Cocaine Selective Severity Assessment (CSSA), Zung Self-Rating Anxiety Scale, Beck Depression Inventory (BDI), Symptom Checklist-90 (SCL-90), and the Insomnia Severity Index. Results: After four weeks of rTMS treatment, 9 out of 16 subjects (56.25%) had a negative urinalysis test, with a significant conversion rate with respect to baseline (Z = -3.00; p = 0.003). Craving scores significantly improved only at T2 (p = 0.020). The overall psychopathological burden, as measured by the SCL-90 Global Severity Index (GSI), significantly decreased during the study period (Z = -2.689; p = 0.007), with a relevant improvement with regards to depressive symptoms, anhedonia, and anxiety. Subjects exhibiting lower baseline scores on the SCL-90 were more likely to be in the positive outcome group at the end of the study (Z = -3.334; p = 0.001). Discussion: Findings from this study are consistent with previous contributions on rTMS use in subjects with cocaine use disorder. We evidenced a specific action on some psychopathological areas and a consequent indirect effect in terms of relapse prevention and craving reduction. A double-blind, sham-controlled, neuro-navigated rTMS study design is needed, in order to confirm the potential benefits of this technique, opening new scenarios in substance use disorders treatment.